Consensus guidelines for antifungal prophylaxis in haematological malignancy and haemopoietic stem cell transplantation, 2021. (22nd December 2021) - Teh, Benjamin W.; Yeoh, Daniel K.; Haeusler, Gabrielle M.; Yannakou, Costas K.; Fleming, Shaun; Lindsay, Julian; Slavin, Monica A.
Abstract: Antifungal prophylaxis can reduce morbidity and mortality from invasive fungal disease (IFD). However, its use needs to be optimised and appropriately targeted to patients at highest risk to derive the most benefit. In addition to established risks for IFD, considerable recent progress in the treatment of malignancies has resulted in the development of new 'at‐risk' groups. The changing epidemiology of IFD and emergence of drug resistance continue to impact choice of prophylaxis, highlighting the importance of active surveillance and knowledge of local epidemiology. These guidelines aim to highlight emerging risk groups and review the evidence and limitations around new formulations of established agents and new antifungal drugs. It provides recommendations around use and choice of antifungal prophylaxis, discusses the potential impact of the changing epidemiology of IFD and emergence of drug resistance, and future directions for risk stratification to assist optimal management of highly vulnerable patients.